Pengaruh Ekspor Dan Impor Terhadap Neraca Perdagangan Di Indonesia - Arifudin Arifudin; Salsa Nurhidayah; Sintiya Sintiya; Afifudin Afifudin; Arif Naofal Nabih (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Indonesia has a direct relationship with export and import activities. The trade balance includes export and import activities, being a record that records all product transactions carried out by a country. As an important instrument, the trade balance provides a comprehensive picture of a country's export and import situation. When exports are less than imports, it is called a deficit, conversely, if exports are greater than imports, it is called a surplus. When exports and imports are balanced, the trade balance is considered equal. This research aims to identify the impact of imports and exports on Indonesia's trade balance in 2021. The research method applied is a quantitative approach, by collecting data and information from various sources and literature. The data was then processed and analyzed using a multiple linear regression model with the SPSS 25 software package and its data analysis capabilities. From the research results, it was found that the significance value of exports and imports was 0.00, which shows that exports and imports have quite a large influence on the trade balance in Indonesia. namely 0.921.